2005
DOI: 10.1099/mic.0.27838-0
|View full text |Cite
|
Sign up to set email alerts
|

Sulfoacetaldehyde is excreted quantitatively by Acinetobacter calcoaceticus SW1 during growth with taurine as sole source of nitrogen

Abstract: Eighteen enrichment cultures with taurine (2-aminoethanesulfonate) as the sole source of combined nitrogen under aerobic conditions were all successful, and 24 pure cultures were obtained. Only three of the cultures yielded an inorganic product, sulfate, from the sulfonate moiety of taurine, and the others were presumed to yield organosulfonates. Sulfoacetate, known from Rhodopseudomonas palustris CGA009 under these conditions, was not detected in any culture, but sulfoacetaldehyde (as a hydrazone derivative) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 23 publications
(41 citation statements)
references
References 32 publications
(46 reference statements)
0
40
0
Order By: Relevance
“…They were inoculated with washed activated sludge from the aeration tank of the wastewater treatment plant in Konstanz, Germany, or with material from grassland soil or garden soils (from Switzerland and Germany) or littoral sediment from Lake Constance (Thurnheer et al, 1986). Enrichment cultures with N-methyltaurine as the sole source of fixed nitrogen for growth, and the standard isolation procedure, were described elsewhere (Weinitschke et al, 2005).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…They were inoculated with washed activated sludge from the aeration tank of the wastewater treatment plant in Konstanz, Germany, or with material from grassland soil or garden soils (from Switzerland and Germany) or littoral sediment from Lake Constance (Thurnheer et al, 1986). Enrichment cultures with N-methyltaurine as the sole source of fixed nitrogen for growth, and the standard isolation procedure, were described elsewhere (Weinitschke et al, 2005).…”
Section: Methodsmentioning
confidence: 99%
“…They were inoculated with washed activated sludge from the aeration tank of the wastewater treatment plant in Konstanz, Germany, or with material from grassland soil or garden soils (from Switzerland and Germany) or littoral sediment from Lake Constance (Thurnheer et al, 1986). Enrichment cultures with N-methyltaurine as the sole source of fixed nitrogen for growth, and the standard isolation procedure, were described elsewhere (Weinitschke et al, 2005).Cells were grown in 50 ml or 200 ml cultures in Erlenmeyer flasks, harvested, washed and ruptured by passage through a French pressure cell at 138 MPa; whole cells and debris were removed by centrifugation (10 min, 15 000 g, 4 uC) to yield crude extract (Denger et al, 2004a). Membrane (particulate) and soluble fractions were obtained by ultracentrifugation (200 000 g, 30 min, 4 uC).…”
mentioning
confidence: 99%
“…We also tested whether the sulfonates could serve as sole sources of combined nitrogen for growth (cf. Weinitschke et al 2005). D. acidovorans NAT assimilated nitrogen from N-acetyltaurine, taurine or acetamide, but not from cysteate, 3-aminopropanesulfonate or N-methyltaurine.…”
Section: Resultsmentioning
confidence: 93%
“…3a, b). The assimilation of taurine-nitrogen sometimes involves utilization of the compound concomitant with growth, as found in Acinetobacter calcoaceticus SW1, Alcaligenes faecalis MT1 and Rhodococcus opacus ISO-5 (Denger et al, 2004a;Weinitschke et al, 2005Weinitschke et al, , 2006, and sometimes with excretion and subsequent utilization of the ammonium ion as in Rhodopseudomonas palustris CGA009 (Denger et al, 2004b), as shown in Fig. 3(b).…”
Section: Discussionmentioning
confidence: 93%
“…The compound can also serve as a sole source of sulfur for growth (e.g. Kertesz, 2000), and a range of phenomena can be involved when organisms utilize the compound as a sole source of nitrogen; these include deamination without desulfonation, not always concomitant with substrate utilization (Denger et al, 2004b;Styp von Rekowski et al, 2005;Weinitschke et al, 2005), and utilization concomitant with taurine carbon (Denger et al, 2004a). Two general pathways for the dissimilation of taurine have been hypothesized , one of which has received significant experimental support in Silicibacter pomeroyi DSS-3, especially for the genes encoding an ATP-binding cassette transporter (TauABC), taurine : pyruvate aminotransferase (Tpa) and alanine dehydrogenase (Ald) (analogous to Fig.…”
Section: Introductionmentioning
confidence: 99%